PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI SARAUKE SUB TEMA KERAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU PESERTA DIDIK KELAS 4 SEKOLAH DASAR - Windi Retno Wandani; Iqnatia Alfiansyah (Universitas Muhammadiyah Gresik, 2020)
This development research aims to determine the effectiveness of Sarauke Monopoly learning media sub-themes of ethnic and religious diversity in my country in class 4 elementary school students. The process of developing learning media uses a modified and simplified 4-D model, namely, defining, developing, and without disseminating. The results of the development of learning media in the form of the Sarauke Monopoly. The data source in this development research is the fourth grade students of Gulomantung Elementary School, amounting to 34 students. Data collection used is learning media validation, student response questionnaires, and learning outcomes tests. With data analysis, namely, analyzing the validity of learning media, analyzing the practicality of learning media, and the effectiveness of learning media.Based on the results of descriptive analysis of data from the validation and trial data, it wasfound that the development of Sarauke Monopoly learning media for the material on theme 7 subtheme1 learning 3 grade IV Gulomantung Elementary School fulfilled the good criteria, which were asfollows: the validator gets a percentage of 78.88% which is categorized as valid and can be usedduring the learning process learning completeness analysis, the results of classical learningcompleteness percentage of 90.625%, it can be said that students 'mastery learning is achieved, andthe percentage of students' response to Sarauke's Monopoly learning media by 97.26% can be said tobe positive.